2016
DOI: 10.1186/s12891-016-0917-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of venous thromboembolism and hemorrhage related safety studies of preoperative anticoagulation therapy in hip fracture patients undergoing surgical treatment: a case–control study

Abstract: BackgroundVenous thromboembolism is a common postoperative complication following orthopedic surgeries, with morbid and potentially fatal consequences. Perioperative low-molecular-weight heparin (LMWH) therapy can reduce the incidence of venous thromboembolism, but may also increase the risk of bleeding complications. Current literature reflects the need to balance the improved efficacy of early initiating prophylaxis with increased risk of perioperative bleeding. The purpose of this study was to compare the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…This reinforces the aggravating characteristics of patients submitted to this type of surgery. [26][27] Low preoperative hemoglobin levels was another aggravating factor for individuals with femur fractures. A retrospective study with 7,420 patients showed an increase in 30-day mortality in patients with low hemoglobin levels on admission, even after correcting for comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This reinforces the aggravating characteristics of patients submitted to this type of surgery. [26][27] Low preoperative hemoglobin levels was another aggravating factor for individuals with femur fractures. A retrospective study with 7,420 patients showed an increase in 30-day mortality in patients with low hemoglobin levels on admission, even after correcting for comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…31 Although the study showed significant risk of interoperative hypotension, similar to the results of the present study, in which hypotension was the most frequent complication, and that epidural anesthesia is still the main choice of and moat recommended type of anesthesia for this type of surgery. [25][26]32 Regarding time in days between date of admission and date of surgery, differences were found between Brazilian and international studies, with means between 1.44 and 19 days. It is worth emphasizing that delays in femur fracture repair surgery greater than 48 hours increase the risk of complications and can result in greater one-year mortality rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical practice involving the use of anticoagulants, e.g., dosing, timing, and managing complications, has been a real challenge even to some of the best experts in the field mainly due to their potential to cause serious adverse effects, both hemorrhagic and nonhemorrhagic which may occur with all the currently used anticoagulants regardless of their year of discovery [2,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%